Gammaherpesvirus in Cervid Species from Norway: Characterization of a New Virus in Wild and Semi-Domesticated Eurasian Tundra Reindeer (Rangifer tarandus tarandus) - Das Neves, Carlos G; Sacristan, Carlos; Madslien, Knut Ivar Engesæter; Tryland, Morten (Viruses, 2020)
Gammaherpesvirus infections have been described in cervids worldwide, mainly the genera Macavirus or Rhadinovirus . However, little is known about the gammaherpesviruses species infecting cervids in Norway and Fennoscandia. Blood samples from semi-domesticated ( n = 39) and wild ( n = 35) Eurasian tundra reindeer ( Rangifer tarandus tarandus ), moose ( Alces alces , n = 51), and red deer ( Cervus elaphus , n = 41) were tested using a panherpesvirus DNA polymerase (DPOL) PCR. DPOL-PCR-positive samples were subsequently tested for the presence of glycoprotein B (gB) gene. The viral DPOL gene was amplified in 28.2% (11/39) of the semi-domesticated reindeer and in 48.6% (17/35) of the wild reindeer. All moose and red deer tested negative. Additionally, gB gene was amplified in 4 of 11 semi-domesticated and 15 of 17 wild Eurasian reindeer DPOL-PCR-positive samples. All the obtained DPOL and gB sequences were highly similar among them, and corresponded to a novel gammaherpesvirus species, tentatively named Rangiferine gammaherpesvirus 1 , that seemed to belong to a genus different from Macavirus and Rhadinovirus . This is the first report of a likely host-specific gammaherpesvirus in semi-domesticated reindeer, an economic and cultural important animal, and in wild tundra reindeer, the lastpopulation in Europe. Future studies are required to clarify the potential impact of this gammaherpesvirus on reindeer health.